MASS LAYOFF MANAGEMENT AT DOMESTIC ENTERPRISES - Yulia Sotnikova; Eka Stepanova; Nikita Nazarov (Сучасний стан наукових досліджень та технологій в промисловості, 2018)
The subject of the study is to analyze the behaviour of employees in the context of personnel reduction taking into account the current transformational conditions of the business environment of Ukrainian enterprises. The goal of the study is to identify the ways to overcome the problem of mass layoffs considering the peculiarities of the domestic labour market development. The objective is to set up a commission to facilitate the process of reemployment of laid-off employees and specify its place in resolving labour disputes and conflicts within the National Mediation and Reconciliation Service (NMRS); to determine the main stages for implementing the strategy of employee layoffs focusing on suggested measures and the areas of responsibility of authorized people; to create a pattern for the relationship among employees who need assistance and those institutions that carry it out. While dealing with the problem such common scientific methods are used as the system, graphical and structural analysis. The following results are obtained: the expediency of implementing the strategy of behaviour of the subjects of social and labor relations in the case of employee layoffs is justified; under the conditions of transformations, due attention should be paid to the development of a strategy for employee layoffs so that the whole procedure is carried out in accordance with European requirements and standards; the structure of the commission which is in charge for decisions on the issues of reemployment is presented; the sequence of stages for implementing the strategy of behaviour of subjects of social and labour relations in the event of employee layoffs is developed. Conclusions. The implementation of the rapid response strategy will make the process of employee laying off the most comfortable for all participants: redundant personnel will get psychological support; the local community will reduce the rate of unemployment in the region.